Enzyme-Linked Immunosorbent Assay (ELISA): Basic Principle And Clinical Significance In The Field Of Medical Rsearch (International Journal of Food and Nutritional Sciences, 2022)
Background: The enzyme-linked immunosorbent assay (ELISA), and in particular its application to as diagnostic tools in medical science, has considered as gold standard of immunoassay. Further, ELISA are also used as analytical and quality assurance tools in biomedical research for the detection and quantification of various markers in a given sample which is present in very small quantities. Development of ELISA also make way for the estimation of countless other biological molecules, such as hormones and proteins. ELISA seems practical, easy to perform, and quite sensitive. Inspiring results have been achieved with ELISA in initial collaborative studies and in some field applications in medical research.Methods: This review is carried out through a non-systematic search of the available literature, will offer an overview of the existing information of ELISA and its clinical use, also exploring the future outlook of the dynamic role of ELISA in the field of medical research.Results and Conclusion: This review summarizes the role of ELISA and their role in diagnosis. From this we can say that in current scenario ELISA is integral part of medical science and in future help in improvising of medicine.